Bilateral trifocal IOL implantation in a pediatric case of cataract following steroid-therapy for acute lymphoblastic leukemia - Yildirim, Timur Mert; Auffarth, Gerd U.; Son, Hyeck Soo; Huber, Christian; Beisse, Flemming; Khoramnia, Ramin (American journal of ophthalmology. Case reports, 2019)
Purpose - To present the case of a 9-year-old child with bilateral posterior subcapsular cataract developed through steroid treatment for acute lymphoblastic leukemia. Cataract surgery with trifocal intraocular lens implantation was performed in both eyes. - Observations - Uncorrected distance visual acuity increased from +0.3 and + 0.4 logMAR preoperatively to 0.00 and + 0.04 logMAR after surgery. Binocular uncorrected values for intermediate and near visual acuity were −0.04 logMAR and 0.02 logMAR after surgery, respectively. The patient did not report side effects like halos or glare and was able to participate in his daily activities (school and sports) without spectacles. - Conclusions and Importance - This report represents the first description of a bilateral implantation of trifocal intraocular lenses in a pediatric cataract case with restoration of visual function in far, intermediate and near distance. Trifocal intraocular lenses to compensate for the loss of accommodation can be an option in selected cases of children with cataract.